Can subjective data improve inequality measurement? A multidimensional index of economic inequality - Philipp Poppitz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This work addresses the normative and empirical problems when measuring multidimensional inequality. In contrast to previous works, individuals' perception of inequality is used to estimate a weights for five dimensions based on German microdata. Using the estimated hedonic weights, the results show that annual multidimensional economic inequality is lower than income inequality, but significantly higher than inequality based on equal weights and increases with greater substitution elasticity.
Keywords: D31; 330